Leveraging exceptions and limitations for digital curation and online collections: the U.S. case (Libellarium: journal for research in the field of information and related sciences, 2017)
Librarians wanting to use digital affordances for their patron’s and public benefit have increasingly found themselves frustrated by copyright law designed for a pre-digital era. In the U.S., this frustration has driven the nation’s most prestigious library group, the Association of Research Libraries, to explore the utility of the major exception to copyright monopoly rights, fair use, in order to accomplish basic curation and collection goals in a digital era. The ARL’s efforts to clarify how libraries can employ fair use has resulted in sometimes-dramatic changes in how work is done, and has permitted innovation at some universities. Its approach demonstrates the power of consensus in a professional field to permit innovation within the law.
Keywords: library; copyright; fair use; user rights; digital; curation; collection; norms